PERTUMBUHAN VEGETATIF BIBIT JERUK GERGA PASCA OKULASI PADA KONSENTRASI PUPUK ORGANIK CAIR YANG BERBEDA - Lia Resti Utami; Yulian Yulian; Bambang Sulistyo (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[VEGETATIVE GROWTH OF GRAFTING SEEDLINGS OF GERGA ORANGE IN DIFFERENT CONCENTRATIONS OF LIQUID ORGANIC FERTILIZER]. This study aims to examine explain the effect of gamal leaf liquid organic fertilizer dosage, the way of application of gamal leaf liquid organic fertilizer, and the interaction between treatments on the growth of citrus plants. This research was conducted from August to December 2017 at the Greenhouse of the Faculty of Agriculture, University of Bengkulu. This research was carried out using a Randomized Complete Block Design using 2 factors. The first factor is the way the application of gamal leaf liquid organic fertilizer is sprayed on the leaves and watered onto the ground. The second factor is the concentration of gamal leaf liquid organic fertilizer which consists of control, 25%, 50%, 75% and 100%. The results showed that application of liquid organic fertilizer only gave effect to the number of branches. The 50% gamal leaf liquid organic fertilizer concentration was able to increase the number of branches of gerga orange seedlings by an average of 1.04 branches.